Stimulation of P2X7 Enhances Whole Body Energy Metabolism in Mice - Giacovazzo, Giacomo; Fabbrizio, Paola; Apolloni, Savina; Coccurello, Roberto; Volonté, Cinzia (Frontiers in Cellular Neuroscience, 2019)
The P2X7 receptor, a member of the ionotropic purinergic P2X family of extracellular ATP-gated receptors, exerts a strong trophic effect when tonically activated in cells, in addition to a cytotoxic role after sustained activation. Because of a widespread distribution, P2X7 regulates several different cell- and tissue-specific physiological functions, and is involved in a number of disease conditions. A novel role has recently emerged for P2X7 in the regulation of glucose and energy metabolism. In previous work, we have demonstrated that genetic depletion, and to a lesser extent also pharmacological inhibition of P2X7, elicits a significant decrease of whole body energy expenditure and an increase of respiratory exchange ratio. In the present work, we have investigated the effects of P2X7 stimulation in vivo on whole body energy metabolism. Adult mice were daily injected with the specific P2X7 agonist 2′(3′)-O-(4-Benzoylbenzoyl)adenosine5′-triphosphate for one week and subjected to indirect calorimetric analysis for 48 hours. We report that 2′(3′)-O-(4-Benzoylbenzoyl)adenosine5′-triphosphate increases metabolic rate and O2 consumption, concomitantly decreasing respiratory rate and upregulating NADPH oxidase 2 in gastrocnemius and tibialis anterior muscles. Our results indicate a major impact on energy homeostasis and muscle metabolism by activation of P2X7.